Role of Crystallographic Anisotropy in the Formation of Surface Layers of Single NiTi Crystals after Ion-Plasma Alloying; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Poletika T. M.; Meisner L. L.; Girsova S. L.; Meisner S. N.; Shulepov I. A. Ivan Anisimovich (2015, 2015)
Title screen